The variance of the amino acids in some lucerne (Medicago sativa L.) populations - Babinec J.; Kozová Z.; Straková E.; Suchy P. (Quality in lucerne and medics for animal production, 2001)
It is probably theoretically possible to select lucerne materials with the better amino acid composition for the different uses. The highest coefficients of variance were observed for isoleucin (31.52), phenylalanin (30.43), arginin (30.35) and methionin (25.88). It is necessary to check the heredity of these traits. The differences in the total content of the amino acids among populations were from 85.89 to 110.11 per cent (100 per cent equal to 39233 g per kg). The highest total content of amino acids and the content of indispensable amino acids was observed in populations ZE 24.5, Palava, N 2 III, SAP II and HOL´Y 1.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)